Pharmacokinetic and Pharmacodynamic Evaluation of the Drug‐Drug Interaction Between Isavuconazole and Warfarin in Healthy Subjects. Issue 1 (4th August 2016) - Desai, Amit; Yamazaki, Takao; Dietz, Albert J.; Kowalski, Donna; Lademacher, Christopher; Pearlman, Helene; Akhtar, Shahzad; Townsend, Robert
Abstract: This phase 1 trial evaluated pharmacokinetic and pharmacodynamic interactions between the novel triazole antifungal agent isavuconazole and warfarin in healthy adults. Multiple doses of isavuconazole were administered as the oral prodrug, isavuconazonium sulfate (372 mg 3 times a day for 2 days loading dose, then 372 mg once daily thereafter; equivalent to isavuconazole 200 mg), in the presence and absence of single doses of oral warfarin sodium 20 mg. Coadministration with isavuconazole increased the mean area under the plasma concentration‐time curves from time 0 to infinity of S‐ and R‐warfarin by 11% and 20%, respectively, but decreased the mean maximum plasma concentrations of S‐ and R‐warfarin by 12% and 7%, respectively, relative to warfarin alone. Mean area under the international normalized ratio curve and maximum international normalized ratio were 4% lower in the presence vs absence of isavuconazole. Mean warfarin area under the prothrombin time curve and maximum prothrombin time were 3% lower in the presence vs absence of isavuconazole. There were no serious treatment‐emergent adverse events (TEAEs), and no subjects discontinued the study due to TEAEs. All TEAEs were mild in intensity. These findings indicate that coadministration with isavuconazole has no clinically relevant effects on warfarin pharmacokinetics or pharmacodynamics.